THE SCIENTIFIC LINGUISTIC EXPERTISE: COMPARATIVE ANALYSIS - Medinayeva, Ақерке Аманқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2017)
In the Republic of Kazakhstan projects laws and projects international treaties developed by public authorities, on the official Russian language, after which the work is under way to ensure their translation into the official language. Bills or draft international treaties fully considered and finalized all the concerned authorities, if necessary, they make changes and additions. Then rises the issue of the translation into Kazakh laws and of international treaties. Typically, the translation of the draft law or international treaty of the project, designed in Russian, given only a few days, during which time the translator translates the text, but does not have time to refine. Moreover, sometimes in the course of the translation of the text of the bill into the Kazakh language have to involve a lawyer, bilingual and knowledgeable, understanding the specific features of the sphere of social relations, which are regulated by the bill. Otherwise, do not avoid the distorted translation of the legal norm set out in the bill. In this connection it is obvious inclusion of a number of scientific expertise of scientific linguistic expertise in order to improve the wording of the bill text in the Kazakh language It should be appreciated that the determination of the legal basis of the scientific linguistic expertise on bills and drafts of international treaties is a must, along with other types of scientific expertise This article specifies the purpose and procedures, conditions and features, as well as the similarities and differences conduct of scientific linguistic expertise in our country, and the Russian Federation. In addition, examples of the shortcomings identified in the course of scientific linguistic expertise on the text of the bill in the Kazakh language in order to bring them to the attention of staff employees to translation of the draft law on the Kazakh language and avoid this in the future. The article will contribute to improving the quality of the editorial board of the bill on the state language